Planning Application with Voice Recognition to Assist Procrastinators in Managing Time - Kayalvily, Tabianan; Soh, Kah Yew; Deshinta, Arrova Dewi (INTI International University, 2018)
This paper studies the way of life of a procrastinator and its management of time. Procrastinator refers to human behavior who like to delay or postpone actions. Many studies have been conducted about how to overcome the act of procrastination. Majorly, they use psychological approaches that lead to motivation like forgive yourself, commit to the task, act as you go, minimize distraction, etc. According to the American Psychological Association, approximately 80% to 95% of college students procrastinate their college works. Since college students are very much close with technology, this paper attempts to overcome the procrastination with the help of current technology i.e. mobile apps. It is believed that time management is the core issue of procrastination so the mobile apps are developed as a personal time planning application using voice recognition technology to simplify the tasks. The significant feature of this app is that the procrastinator users (PU) does not require to type the commands into the mobile phones but just use voice as input. The Time Planning Application (TPA) translates the voice input into text input and create a simple time schedule accordingly. The notification of the scheduled tasks is provided so that the PU is always reminded about what task to do. By having simplification acts to create time management (using voice) plus a constant reminder, this paper attempts to motivate the procrastinator to manage their time better. The TPA is developed using Android studio with an online database attached to 000webhosting and PHP (Hypertext Preprocessor) scripting language for development